2000
DOI: 10.1046/j.1365-2826.2000.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐Independent, Tyrosine Phosphorylation‐Dependent Effects of Serum on the Morphology of Cultured Neurohypophysial Astrocytes

Abstract: Activation of adenylate cyclase induces cultured neurohypophysial astrocytes (pituicytes) to change from a protoplasmic, nonstellate form to a stellate form. Stellation is inhibited and reversed (destellation) by serum. The objective of the present studies was to examine the roles of Ca2+ and tyrosine phosphorylation in mediating these morphological changes. The effects of forskolin (to induce stellation) and serum (to inhibit and reverse stellation) were not affected by replacement of Ca2+ with Co2+ in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that thrombin‐stimulated morphological change is a primary result of the G 12/13 ‐mediated MLC phosphorylation that leads to actin rearrangement (Majumdar et al, 1998). In addition, a previous study by Seasholtz et al (2004) revealed modulation of cell rounding by the G i/o and G q/11 pathways. In the case of thrombin‐induced morphological changes, these authors mentioned the weak coupling between cell rounding and the G i/o pathway and the potent link between cell rounding and the G q/11 pathway involving PLC activation and PIP 2 breakdown.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies have shown that thrombin‐stimulated morphological change is a primary result of the G 12/13 ‐mediated MLC phosphorylation that leads to actin rearrangement (Majumdar et al, 1998). In addition, a previous study by Seasholtz et al (2004) revealed modulation of cell rounding by the G i/o and G q/11 pathways. In the case of thrombin‐induced morphological changes, these authors mentioned the weak coupling between cell rounding and the G i/o pathway and the potent link between cell rounding and the G q/11 pathway involving PLC activation and PIP 2 breakdown.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, we postulate that bidirectional regulation might allow the cells to rapidly accommodate their elastic morphology. In the view of Ca 2+ dynamics, previous studies indicated that extensions of astrocytic protrusions (stellation) induced by dibutyryl cyclic AMP, forskolin, or amyloid beta peptide were independent of extracellular Ca 2+ (Ramsell and Cobbett, 2000; Abe and Saito, 2001), implying that bidirectional motions can be distinguished by their dependence on Ca 2+ entry. Thus, TRPC3 might contribute to the mechanism of thrombin‐induced advancing retraction rather than retraction‐induced counter‐reextension in astrocytoma cells.…”
Section: Discussionmentioning
confidence: 99%